S100A4 is elevated in axial spondyloarthritis: a potential link to disease severity - Šumová, Barbora; Cerezo, Lucie Andrés; Hulejová, Hana; Prajzlerová, Klára; Tomčík, Michal; Bubová, Kristýna; Štěpán, Jan; Filková, Mária; Kropáčková, Tereza; Grigorian, Mariam; Pavelka, Karel; Vencovský, Jiří; et al. (BMC rheumatology, 2020)
BACKGROUND: S100A4 is a member of calcium binding S100 protein family well known for its role in cancer progression and metastasis. Nevertheless, S100A4 also serves as a negative regulator of bone formation. Dickkopf-1 (DKK-1), marker of bone remodelling, is also implicated in the process of syndesmophyte formation in ankylosing spondylitis. The aim of our study was to evaluate plasma levels of S100A4 in patients with axial spondyloarthritis and to determine the potential association of S100A4 with disease severity, clinical manifestations and with bone changes in a cross-sectional study. METHODS: Fifty-eight patients with axial spondyloarthritis and 40 healthy controls were studied. Biological samples were analysed for S100A4 and Dickkopf-1. Disease activity was assessed according to the Bath Ankylosing Spondylitis Disease Activity Index. C-reactive protein (CRP) was used as a marker of inflammation. Radiographic damage was assessed using the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). RESULTS: The plasma levels of S100A4 were significantly higher in patients with axial spondyloarthritis compared to heathy controls (p < 0.0001). The levels of S100A4 were higher in early stages of the disease and lower in patients with the presence of syndesmophytes (p = 0.009). Furthermore, we found weak but significant inverse correlation of plasma S100A4 with the mSASSS (r = - 0.363, p = 0.030). Levels of S100A4 were negatively associated with disease duration (r = - 0.404, p = 0.002) and positively with Dickkopf-1 binding capacity (r = 0.312, p = 0.023). CONCLUSIONS: This is the first study showing elevated circulating levels of S100A4 in patients with axial spondyloarthritis, particularly in early stages of the disease prior to spinal involvement, and its significantly lower levels in patients with syndesmophytes. The role of S100A4 in the pathogenesis of axial spondyloarthritis can be suggested.
Keywords: Syndesmophyte; S100A4; Disease duration; Axial spondyloarthritis; Disease severity